The Beneficial Effect of Praeruptorin C on Osteoporotic Bone in Ovariectomized Mice via Suppression of Osteoclast Formation and Bone Resorption - Liu, Xuqiang (Front Pharmacol, 2017)
Being a highly prevalent disease, osteoporosis causes metabolism defects. Low bone density, compromised bone strength, and an increased danger of fragility fracture are its main characteristics. Natural compounds have been considered as potential alternative therapeutic agents for treating osteoporosis. In this study, we demonstrated that a natural compound, praeruptorin C (Pra-C), derived from the dried roots of Peucedanum praeruptorum, has beneficial effects in suppressing osteoclast formation and resorption function via attenuating the activation of nuclear factor kappa B as well as c-Jun N-terminal kinase/mitogen-activated protein kinase signaling pathways. Moreover, Pra-C was tested in the ovariectomized (OVX) mice, a well-established model of post-menopausal bone loss, and the results indicated Pra-C exerted beneficial effects on inhibiting excessive osteoclast activity and increasing bone mass of OVX mice. Therefore, the protective effects of Pra-C on OVX mice bone are related to its inhibition of osteoclast formation and bone resorption, suggesting that Pra-C is a good potential candidate for osteoporosis treatment.